(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The article describes the essence of tax potential and the digital economy in modern conditions. An analysis of the tax potential and digital services in the global economy was carried out. The results of scientific research in the field of formation of the concept of tax potential taking into account the digital economy are reflected. The main characteristics of digital services are shown in the context of the ongoing pandemic and military special operations in Ukraine. Important conclusions have been drawn regarding the problems of tax potential and the digital economy.